Factors Influencing Purchase Intention with Brand Image Moderation on Hotto Purto in Surabaya - Stefanny Widjaja; Dewi Surya Wuisan (International Journal of Economics Accounting and Management, 2025)
This study aims to analyze the factors that influence purchase intention on Hotto Purto products in Surabaya with Brand Image as a moderating variable. The factors analyzed are Electronic Word of Mouth (eWOM), Perceived Quality, and Consumer Confidence. The role of Brand Image is tested in strengthening the influence of these three factors on consumer purchase intention. The method used in this study is a quantitative approach with data collection through questionnaires distributed to Hotto Purto consumers in Surabaya. The collected data were then analyzed using regression analysis techniques and moderation tests to test the relationship between the variables studied. The results showed that eWOM, Perceived Quality, and Consumer Confidence have a positive and significant influence on Brand Image. In addition, Brand Image acts as a moderating variable that strengthens the influence of these factors on purchase intention. These findings indicate that a positive brand image, formed by information from eWOM, perceived quality, and consumer trust levels, can increase product purchase intention. This study contributes to marketing theory by identifying the important role of Brand Image in strengthening the influence of factors that influence purchase intention